THE ANALYSIS OF STUDENTS’ E-LEARNING READINESS ON ENGLISH LEARNING PROCESS - Mahendrayana, Gede; Sintya Dewi, Kadek (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2021)
The process of English Learning before and during Covid-19 pandemic is very difference. The learning process which is conducted at school has changed into distance learning process. All schools are required to implement e-learning to support the distance learning process. This study was aimed at analyzing students’ e-learning readiness toward the implementation of e-learning at SMK Negeri 1 Kubutambahan. A mixed-method research design utilizing concurrent embedded model which is a quantitative method as a primer method was employed in this study. A questionnaire of students’ e-learning readiness and an observation sheet were used to collect the data. The obtained data were then analyzed quantitatively and qualitatively. The result of the study showed that the readiness of SMK Negeri 1 Kubutambahan students in using e-learning in the context of distance learning is classified on ready category which still needs some improvement. From the four aspects of readiness assessed, there is one aspect that belongs to unready category that requires a little improvement, namely the technological aspect. Meanwhile, the other three aspects, namely aspects of innovation, people, and self-development belong to the ready category which requires a little improvement in its implementation.